From Oxadiazole to Triazole Analogues: Optimization toward a Dual Orexin Receptor Antagonist with Improved in vivo Efficacy in Dogs. (16th January 2020) - Brotschi, Christine; Bolli, Martin H.; Gatfield, John; Heidmann, Bibia; Jenck, Francois; Roch, Catherine; Sifferlen, Thierry; Treiber, Alexander; Williams, Jodi T.; Boss, Christoph
Abstract: The orexin system is responsible for regulating the sleep‐wake cycle. Suvorexant, a dual orexin receptor antagonist (DORA) is approved by the FDA for the treatment of insomnia disorders. Herein, we report the optimization efforts toward a DORA, where our starting point was (5‐methoxy‐4‐methyl‐2‐[1, 2, 3]triazol‐2‐yl‐phenyl)‐{(S)‐2‐[5‐(2‐trifluoromethoxy‐phenyl)‐[1, 2, 4]oxadiazol‐3‐yl]‐pyrrolidin‐1‐yl}methanone (6 ), a compound which emerged from our in‐house research program. Compound 6 was shown to be a potent, brain‐penetrating DORA with in vivo efficacy similar to suvorexant in rats. However, shortcomings from low metabolic stability, high plasma protein binding (PPB), low brain free fraction (fu brain), and low aqueous solubility, were identified and hence, compound 6 was not an ideal candidate for further development. Our optimization efforts addressing the above‐mentioned shortcomings resulted in the identification of (4‐chloro‐2‐[1, 2, 3]triazol‐2‐yl‐phenyl)‐{(S)‐2‐methyl‐2‐[5‐(2‐trifluoromethoxy‐phenyl)‐4 H ‐[1, 2, 4]triazol‐3‐yl]‐pyrrolidin‐1‐yl}l‐methanone (42 ), a DORA with improved in vivo efficacy compared to 6 . Abstract : DORA explorers : The orexin system plays an important role in regulating the sleep‐wake cycle. Herein we report our optimization efforts toward a novel dual orexin receptor antagonist (DORA) with improved properties over compound 6 . Replacing the oxadiazole by a triazole resulted in compounds (e. g. compound 33 ) with improved properties, such as higher intrinsic metabolic stability, lower plasma protein binding, higher brain free fraction, and increased solubility. Further optimization was needed to decrease the compounds P‐glycoprotein susceptibility. Our work led to the identification of compound 42, a potent, brain‐penetrating DORA with improved in vivo efficacy in dogs compared with compound 6 .